Effects of the termination of LC30 imidacloprid stress on the multigeneration adaptive strategies of Aphis glycines population - Zhang, Aonan; Dou, Nan; Qu, Zhongcheng; Guo, Yongxia; Zhou, WenJing; Wu, Dongxue; Lin, Zhiying; Feng, Min; Cui, Hengjia; Han, Lanlan (Frontiers in Physiology, 2023)
Aphis glycines Matsumura (Hemiptera: Aphididae) is a major soybean pest that often poses a serious threat to soybean production. Imidacloprid is one of the commonly used insecticides to control soybean aphid. To investigate the effect of termination of imidacloprid stress on adaptive strategies of soybean aphid populations. We studied the growth, development and related metabolism changes when the stress was terminated after 24 generations of imidacloprid stress on A. glycines. Results showed that A. glycines population accelerated its recovery and expanded its population size across generation. The longevity of adults of the recovering population in the F12, F18 and F24 generations was 1.11 times, 1.15 times and 1.11 times longer than the control. The fecundity was 10.38%, 11.74% and 11.61% higher than that of the control, respectively. The net reproductive rate (R0) of the recovering population was always significantly higher than that of the control in the F1 to F24 generations. In addition, metabolisms related to the regulation of cell proliferation and oocyte meiosis were significantly up-regulated in the recovering population. Even when the imidacloprid pressure disappeared, intergenerational stimuluses still affected the adaptive strategies of soybean aphid populations. This effect was manifested as inhibiting the growth and development of soybean aphid in the early generations and improving the fecundity of soybean aphid in the later generations. Adaptive soybean aphid populations would surge in the absence of imidacloprid pressure. This study provides an important reference for exploring the adaptability of A. glycines population under termination of stress from low lethal concentrations of imidacloprid, across generations. It also provides important data for monitoring the population dynamics of A. glycines in the field and analyzing the degree of pharmacodynamic stress.